Electron stimulated hydroxylation of a metal supported silicate film. Issue 5 (14th January 2016) - Yu, Xin; Emmez, Emre; Pan, Qiushi; Yang, Bing; Pomp, Sascha; Kaden, William E.; Sterrer, Martin; Shaikhutdinov, Shamil; Freund, Hans-Joachim; Goikoetxea, Itziar; Wlodarczyk, Radoslaw; Sauer, Joachim
Abstract : Low-energy electron irradiation of an ice precovered silicate film enhances surface hydroxylation. Abstract : Water adsorption on a double-layer silicate film was studied by using infrared reflection–absorption spectroscopy, thermal desorption spectroscopy and scanning tunneling microscopy. Under vacuum conditions, small amounts of silanols (Si–OH) could only be formed upon deposition of an ice-like (amorphous solid water, ASW) film and subsequent heating to room temperature. Silanol coverage is considerably enhanced by low-energy electron irradiation of an ASW pre-covered silicate film. The degree of hydroxylation can be tuned by the irradiation parameters (beam energy, exposure) and the ASW film thickness. The results are consistent with a generally accepted picture that hydroxylation occurs through hydrolysis of siloxane (Si–O–Si) bonds in the silica network. Calculations using density functional theory show that this may happen on Si–O–Si bonds, which are either parallel ( i.e., in the topmost silicate layer) or vertical to the film surface ( i.e., connecting two silicate layers). In the latter case, the mechanism may additionally involve the reaction with a metal support underneath. The observed vibrational spectra are dominated by terminal silanol groups ( ν (OD) band at 2763 cm −1 ) formed by hydrolysis of vertical Si–O–Si linkages. Film dehydroxylation fully occurs only upon heating to very high temperatures (∼1200 K) and is accompanied by substantial film restructuring, and even film dewetting upon cycling hydroxylation/dehydroxylation treatment.